An Exposition of the Keynesian System - Scott, Ira O. (Review of Economic Studies, 1951)
Journal Article An Exposition of the Keynesian System Get access Ira O. Scott, Jr. Ira O. Scott, Jr. Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 1, 1950, Pages 12–18, https://doi.org/10.2307/2296266 Published: 01 December 1950